The Uncreated Light of Transfiguration of Our Lord in St. Gregory Palamas’ Thought - Penkov, Dimo (Forum Theologicum Sardicense, 2025)
Dimo Penkov, St. Theodore Studites (759-826) and His Apologetical Approach in the Antirretics (Defense of the Icons). The author analyses the apologetic rhetorical elements in three discourses against those who deny the worship of holy icons. St. Theodore the Studite presents his refutations, which further develop and build upon the arguments of St. John Damascene. The saint outlines the fundamental Christological dimensions of the arguments put forth by Orthodox defenders of holy icons.